The Individual and Combined Effects of Fusaric Acid and T-2 Toxin in Broilers and Turkeys - Ogunbo, S.O.; Broomhead, J.N.; Ledoux, D.R.; Bermudez, A.J.; Rottinghaus, G.E. (International Journal of Poultry Science, 2007)
Two experiments were conducted to evaluate the individual and combined effects of fusaric acid (FA) and T-2 toxin (T-2) in broiler chicks and turkey poults. In each experiment, 80 day-old birds were allotted randomly to a 2×2 factorial arrangement with treatments of 0 and 250 mg FA/kg feed and 0 and 4 mg T-2/kg feed. Diets were fed to 4 pen replicates of 5 birds each for 21 days. Feed intake and body weight gain of poults were reduced (p